Bipolar clavicular fracture on ipsilateral reverse shoulder prosthesis: Case report. (2019) - Maalouly, Joseph; Aouad, Dany; Saade, Jamal; Abboud, Ghadi; El Rassi, Georges
Highlights: Rare case of traumatic bipolar clavicular over an ipsilateral reverse shoulder prosthesis. Open reduction and internal fixation showed satisfactory bony alignement with intact reverse shoulder prosthesis. Post operative rehabilitation is of great importance, taking into consideration the deltoid musculature wish should be addressed for shoulder strengthening over prosthesis. Abstract: Background: Bipolar clavicular fractures are extremely rare with no consensus on management. No previous cases of bipolar clavicular fracture on an ipsilateral reverse shoulder prosthesis have been reported. Case presentation: We report a case of a 78y.o female patient with left bipolar clavicular fracture on ipsilateral reverse shoulder prosthesis, associated with multiple ribs fracture, that was treated with open reduction and internal fixation using k-wires and endobutton for the lateral part, while as the medial part was fixed with plate and screws. Conclusions: Any patient with a clavicle fracture, with a history of sequential forces to the clavicle, a bipolar injury should always be suspected. Attention should be given if any implants are present on the ipsilateral side of the injury, which could affect surgical planning and outcome.